Mechanical properties and freeze-thaw durability of recycled aggregate pervious concrete. (October 2019) - Liu, H B; Li, W J; Yu, H; Luo, G B; Wei, H B
Abstract: Recycled aggregate (RA) was obtained from waste cement concrete brick with the method of crushing and sieving. In order to research the effect of RA content on the properties of pervious concrete, RA was added to replace natural aggregate with equivalent quality method at different levels (25%, 50%, 75% and 100%). The natural aggregate pervious concrete and RA pervious concrete were prepared in the lab. The porosity, permeability, compressive strength, flexural strength and freeze-thaw (F-T) durability of RA pervious concrete were tested. The results indicated that the compressive strength and flexural strength of RA pervious concrete decreased with the increase of RA content. The rapid decreases for compressive strength and flexural strength occurred when the RA content was 25%-75% and 0%-25%, respectively. The porosity and permeability decreased slowly with the increasing RA content. F-T durability of RA pervious concrete was poorer than the natural aggregate pervious concrete. The incorporation levels had negative effect on the F-T durability, but the compressive strength loss of all groups after 25 F-T cycles met the requirement of the national standard. Although the mechanical properties and F-T durability of RA pervious concrete are not satisfied, it can still be used for sidewalks, parks and other light traffic roads.